Antibodies against DNA-psoralen crosslink recognize unique conformation - Hasan, Rashid; Ali, Asif; Ali, Rashid (Biochimica et biophysica acta, 1991)
The DNA-psoralen crosslink induced precipitating antibodies in rabbits with a titer of 1:102400 by direct binding ELISA. The antiserum showed considerable binding with Z-DNA and calf thymus DNA brominated under high salt concentration which has been shown to attain Z-/analogous conformation. Inhibition experiments substantiated the results of direct binding assay. However, the affinity purified IgG showed high degree of specificity for the immunogen and did not recognize nDNA, Z-DNA and brominated DNA as inhibitor. Poly(dG · dC) · poly(dG · dC)-psoralen photoadduct was found to be inhibitory. These results indicate that the antibodies are probably recognizing the unique conformation at the site of psoralen crosslinking. The DNA-psoralen crosslink showed significant binding with SLE sera known to have high levels of anti-native DNA antibodies. Affinity purified SLE-IgG in a competition assay pointed out the autoantibody recognition of altered conformation of DNA-psoralen crosslink.